THE DEVELOPMENT OF READING AND WRITING SKILLS IN SPELLING IRREGULAR WORDS AND CREATIVE THINKING SKILLS OF SECOND GRADE STUDENTS USING BRAIN-BASED LEARNING COMBINED WITH ARTS AND CRAFTS ACTIVITIES - Raksawong , Natthanon; Doungwilai , Dhanita (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This research aimed to 1) develop the skills of reading and spelling words that do not conform to the standard of the second-grade students by 80.00 percent of the students passed the criteria of 80.00 percent or more. 2) develop the skills of writing and spelling words that do not conform to the standard of the second-grade students by 80.00 percent of the students passed the criteria of 80.00 percent or more. 3) develop the skills of creative thinking of the second-grade students by 80.00 percent of the students passed the criteria of 80.00 percent or more. The target group is grade 2 students in the 2024 academic year at Ban Kut Mek School, Udon Thani Province, by purposive selection. This research used the principles of action research. The tools used to collect data include learning management plans, learning management results recording forms, student behavior observation forms, reading skills test that does not correspond to the standard, and writing skills test that does not correspond to the standard. and the assessment of creative thinking skills by using statistics for data analysis including mean, standard deviation and percentage. Qualitative data were analyzed by content analysis. The research results found that 1) the reading and spelling skills of the second-grade primary school students did not meet the standards at 100.00 percent, passing the criteria of 88.00 percent and above. 2) the writing and spelling skills of the second-grade primary school students did not meet the standards at 100.00 percent, passing the criteria of 85.00 percent and above. 3) the creative thinking skills of the second-grade primary school students did not meet the standards at 100.00 percent, passing the criteria of 83.75 percent and above.